Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21203/rs.3.rs-1874878/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultural importance, availability, and conservation status of Spanish medicinal plants. Implications for sustainability

Abstract: The harvest of wild plants with medicinal uses is increasing globally, but we know little of the effects of non-commercial harvesting in their conservation status. Here, we explore the connection between the cultural importance of the 1,376 wild medicinal vascular plants traditionally used in Spain for self-treatment (22% of the autochthonous flora, being 16% endemic) and their availability, conservation, and legal protection status, and discuss the implication of our results for sustainability. A species cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 29 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…Overexploitation is the main threat to the conservation of wild food species [ 3 ], followed by habitat alteration and pollution. Nevertheless, in Spain, studies dealing with the most diverse group of wild plants gathered for traditional medicinal practices have demonstrated that this problem is not of great concern (commercial exploitation excluded) since the vast majority of the species used do not experience problems in their conservation and, with few exceptions, are not included in regional or national conservation laws [ 55 ]. Thus, the same could be said for WEPs.…”
Section: Discussionmentioning
confidence: 99%
“…Overexploitation is the main threat to the conservation of wild food species [ 3 ], followed by habitat alteration and pollution. Nevertheless, in Spain, studies dealing with the most diverse group of wild plants gathered for traditional medicinal practices have demonstrated that this problem is not of great concern (commercial exploitation excluded) since the vast majority of the species used do not experience problems in their conservation and, with few exceptions, are not included in regional or national conservation laws [ 55 ]. Thus, the same could be said for WEPs.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 158 publications (53 journal articles; 58 books; 30 Ph.D. theses; 16 unpublished academic theses; one online database) appearing during 1982–2020 met the aforementioned requirements. The final list covers all the Spanish territory, as ethnobotanical publications were found for all the autonomous communities (the highest level of territorial organization in Spain; Figure 2; Mateo‐Martín et al, 2023: 1. Ethnobotanical references).…”
Section: Methodsmentioning
confidence: 99%
“…The data used in this article can be found at https://doi.org/10.5281/ zenodo.7808167 (Mateo-Martín et al, 2023).…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
See 2 more Smart Citations